Pengaruh Mo dan Ni terhadap Struktur Mikro dan Kekerasan Baja Tahan Karat Martensitik 13Cr [The Effect of Mo And Ni on The Microstructure and Mechanical Properties of 13Cr Martensitic Stainless Steels] - Efendi Mabruri (National Research and Innovation Agency (BRIN), 2015)
Tulisan ini melaporkan pengaruh Mo dan Ni terhadap struktur mikro dan kekerasan baja tahan karat martensitik 13 Cr dengan kondisi temperisasi pada 625oC. Pengamatan struktur mikro dilakukan menggunakan mikroskop optik, SEM-EDS dan uji kekerasan dengan Rockwell C. Penambahan Mo ke dalam baja tahan karat martensitik 13Cr meningkatkan kandungan fasa ferit delta di dalam struktur mikro dan menurunkan kekerasan baja yang bersangkutan. Sedangkan penambahan 3%Ni ke dalam baja tahan karat martensitik 13Cr yang mengandung 3%Mo menurunkan kandungan fasa ferit delta di dalam struktur mikro dan meningkatkan kekerasan. Karbida logam yang terbentuk merupakan senyawa M23C6 dan penambahan 3%Mo menurunkan kandungan Cr di dalam karbida logam tersebut akibat substitusi parsial Cr oleh Mo. AbstractThe 13Cr martensitic stainless steels have been widely used for turbine blade materials in steam turbinesystem due to high strength, high toughness and good corrosion resistance.This paper reports the effect of Moand Ni on the microstructure and hardness of 13Cr martenstitic stainless steel in tempered condition at625 °C. Optical microscope and SEM-EDS were used for microstructural observation and Rockwell C forhardness testing. The addition of Mo into 13Cr martensitic stainless steel increased delta ferrite content in themicrostructure and decreased Rockwell C hardness. On the other hand, the addition of Ni into the steelcontaining 3% Mo decreased delta ferrite content and increased the hardness. With respect to metal carbide,EDS analysis confirmed the formation of M23C6 in the steels and Mo addition decreased Cr content in thecarbide due to partial substitution of Cr with Mo